Perioperative magnesium levels in total thyroidectomy and relationship to hypocalcemia. Issue 6 (10th January 2019) - Brophy, Catherine; Woods, Robbie; Murphy, Matthew S.; Sheahan, Patrick
Abstract: Background: We have previously shown an association between hypomagnesemia and hypocalcemia after thyroidectomy. However, little is known regarding the trend in magnesium levels in the days after thyroidectomy. Our objective was to study this trend in magnesium levels after thyroidectomy. Methods: Retrospective review of 173 thyroidectomies with analysis of calcium and magnesium levels on postoperative day 1 (POD1) and POD2. Results: Across the whole group, there was a highly significant decline in magnesium levels between preoperative (0.87 ± 0.06 mmol/L), POD1 (0.80 ± 0.07 mmol/L), and POD2 (0.78 ± 0.08 mmol/L) ( P < .0001). The magnitudes of the magnesium level declines were significantly higher, and the absolute magnesium levels on POD1 and POD2 significantly lower, in patients developing hypocalcemia ( n = 69). Conclusion: Magnesium levels after total thyroidectomy demonstrate a downward trajectory which persists through POD2 and is highly correlated with hypocalcemia. Further study is required to determine if magnesium replacement can alter the course of hypocalcemia in hypocalcemic patients after total thyroidectomy.